NURSES & GROUPS IN THE FAMILY HEALTH PROGRAM: POSSIBILITY OF SOCIAL PARTICIPATION - Maria da Anunciação Silva; Alice G. Bottaro de Oliveira; Edir Nei Teixeira Mandú; Samira Reschetti Marcon (Universidade Federal do Paraná, 2006)
The work with groups, in the Family Health Program, can be considered as a technology of assistance and empowermentof patients and community for the exercise of citizenship. Aim: to analyze in which way the work with groups can generate orstrengthen spaces of community participation and social control. Methods: exploratory-descriptive research in 8 Family Health Unitsfrom Cuiabá/ Brazil. Results: nurses work with groups in current programs in the practice of traditional public health. The groups onlywork with collective information about diseases and treatment and consolidate such assistance strategy while the empowerment dimensionfor the exercise of citizenship is reduced.